Online Learning During the Covid-19 Pandemic at Institute of Health Sciences - Adiesti, Ferlia; Khasanah, Nurun Ayati; Yuliani, Farida; Safitri, Citra Adityarini; Wari, Fitri Edni (LPPM Universitas Prima Nusantara Bukittinggi, 2021)
Â The spread of the virus happened very quickly and caused many victims, so the government made a policy to break the chain in the pandemic. One of the steps recommended by the government is to limit physical and social distance to carry out all activities from their respective homes or what is often referred to as Work from Home (WFH). learning online from home due to the cessation of face-to-face direct learning in class to break the chain and exposure to the coronavirus. This study aims to analyze online learning for STIKES Majapahit Mojokerto students in the Midwifery Study Program.RESEARCH METHODS: This study utilized Qualitative research that is descriptive-analytic in nature and data is taken through Google Form with a student population of STIKES Majapahat Mojokerto Midwifery study program of 58 students.RESULT: This study found results in five respects a. Understanding of material during online lectures that students understand enough about the material given during online lectures. b. communication between lecturers and students during online lectures, communication between lecturers and students goes well, c. The online lecture media used. 6 Applications, d. Electronic devices used for online lectures for students during online lectures are mostly cellphones and e. Constraints in online lectures are obstacles for students in online lectures, which requires a lot of quota due to problems in the weak internet network (Internet Signal), quotas that are highly used by students, conditions are not conducive due to environmental disturbances.CONCLUSION : The results of different studies show that the virtual teaching environment will be successfully used in schools or higher education if it has a suitable and supportive technical environment.Â RECOMMENDATIONS :.This research was conducted in health education which the researcher hopes to be carried out in a wider discussion, for example in this case the use of online learning media in the lar that we studied. The results of our research are expected to bring benefits as a stepping stone in conducting wider research.